ANALYSIS OF THE INFLUENCE OF EDUCATION, HEALTH AND PRODUCTIVITY ON INCOME INEQUALITY IN 34 PROVINCES IN INDONESIA (2015-2021) - Sugiyanto FX; Atria Arie Pamungkas (Jurnal Ekonomi Dan Bisnis, 2023)
Alleviating poverty and income inequality is the essence of development issues and is the main objective of development policies in many countries, including Indonesia. Income inequality is a condition that shows the disproportionate distribution of income from the total income of the Gross Domestic Product (GDP) to the income of households. Therefore, it is necessary to determine the factors that cause income inequality. This study aims to find out (1) The influence of education, health, and productivity on income inequality or the Gini Index; (2) The condition of income inequality inside and outside Java within 2015 – 2021. This study used secondary data obtained from Badan Pusat Statistik and processed using the panel data regression method and the Fixed Effect Model approach with Eviews 12. The results of this study indicate: (1) The distribution of education proxied using data on the average years of schooling has significant and negative influence on income inequality. (2) The health distribution proxied using Life Expectancy Rate data has significant and negative influence on income inequality. (3) Labor productivity has no significant and negative influence on income inequality. (4) Java has a smaller income inequality index compared to provinces outside Java.